Strategi Kepala Sekolah Dalam Meningkatkan Kinerja Tenaga Pendidik Dan Kependidikan - Hidayaturrabbani, Ahmad Wildan (Program Studi Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2023)
This article discusses the management of principal's strategy in improving the performance of educators and education personnel at MarasahTsanawiyah (MTs) Al-Falah Al-Islami Sampang City. The urgency of the principal's strategy in improving teacher performance is to provide an effective and innovative impact in providing guidance, training, and methods that are able to improve the performance of educators and education personnel, either directly to individuals or through external factors. The purpose of this study is to determine and describe 1) The principal's strategy in improving the performance of educators and education staff at Madrasah Tsanawiyah Al-Falah Al-Islami Sampang, 2) Implementation of the principal's strategy in improving the performance of educators and education staff at Madrasah Tsanawiyah Al-Falah Al-Islami Sampang, 3) Factors that support and hinder school principals in improving the performance of educators and education staff at Madrasah Tsanawiyah Al-Falah Al-Islami Sampang, 4) The principal's solution in overcoming the inhibiting factors for the performance of educators and education staff at Madrasah Tsanawiyah Al-Falah Al-Islami Sampang . This type of research is qualitative using a descriptive approach. Data collection techniques carried out include observation, interviews and documentation. The results of this study show that the principal's strategy in improving the performance of educators and education staff at MTs Al-Falah Al-Islami is going well.